Edukasi Peningkatan Nilai Ekonomi Limbah Minyak Goreng Bekas Pakai Melalui Pembuatan Lilin Aromateraphy - Khotim Fadhli; Mar’atul Fahimah; Bekti Widyaningsih; Eka Novita Sari; Arjuna Adi Pratama (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This community service aims to educate partners to increase the economic value of used cooking oil waste into aromatherapy candles so that it leads to a productive economy. Assistance to people who have used a lot of cooking oil in their cooking process plays a strong role in building human resources and quality Indonesian products towards Advanced Indonesia. The priority of partner issues is that there are no products that are produced and become selling points that can lift the partner's economy, due to the lack of knowledge about making aromatherapy candles, especially those that use waste materials. The implementation method in this service is Community Based Research, which is a design that takes place in a community environment and involves community members in the design and implementation of research projects, shows respect for the successful contributions made by community partners, and respects the